A novel endoscopic surgical device for gastric volume reduction bariatric surgery - Kim, Yoonjin; Choi, Hyuk Soon; Kim, Kyungnam; Kim, Byoung Gon; Keum, Bora; Hong, Daehie; Chun, Hoon Jai; Song, Yongnam (International journal of precision engineering and manufacturing, 2016)
Endoscopic bariatric surgeries have been widely studied to minimize surgical invasion to the patients and operation time. Although some of previous endoscopic bariatric devices have reported successful weight loss in animal and human models, operation time in these surgeries was too long for severely obese patients. We aimed to develop a new endoscopic bariatric surgery device that would complete an entire surgery in a short time and provide clinically effective stomach volume reductions. A new anchoring device and suction system were developed from our successive suturing system. Our surgery reduced the fundus area of the stomach by creating a loop of anchors. We performed endoscopic bariatric surgeries in 32 porcine stomachs. Significantly reduced stomach volumes were found following our new bariatric surgeries (before surgery: 999.53±642.39 mm 3 , after surgery: 703.13±445.48 mm 3 , Student’s t-test, p<0.05). Surgery durations were measured to be 14.23±3.01 min in 16 selected stomachs. The new device was tested in three live pigs, and all simulated surgical conditions were successfully completed without any technical difficulties. We successfully developed a new endoscopic device for bariatric surgery, and demonstrated 30% stomach volume reductions, which is comparable volume reductions in clinically proven devices.